Combating Malnutrition through Sustainable Approaches (IntechOpen, 2023)
Malnutrition is the specific condition produced by the intake of too few macronutrients, too many macronutrients (obesity), or inordinate amounts of inappropriate substances such as alcohol. Globally, malnutrition is a major nutritional disorder, especially in developing economies. Poor dietary habits and imbalanced nutrient intake result in adverse consequences on normal body functionality. This book highlights the major causes of malnutrition and how to overcome this problem. Chapters address such topics as energy metabolism and balance, diagnosis of malnutrition, negative effects of malnutrition, sugar and its impact on health, malnutrition in the elderly and children, and much more.